1991
DOI: 10.1002/jsfa.2740540215
|View full text |Cite
|
Sign up to set email alerts
|

Acetylenic compounds in stored packaged carrots

Abstract: Stored carrots vacuum packed in plastic shrink bags showed signijkant variations in the concentration of certain important secondary compounds.in the acetylene group, 18 compounds were isolated and measured. Only eight of these compounds have previously been reported as carrot constituents. The concentrations of 10 of the 18 increased with storage time, and six were present only in stored samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…www.jss-journal.com centration levels of polyacetylenes found in the present study were within the levels previously reported in peeled carrots [13,34]. The carrot peel contained over a ten-fold higher concentration of FaDOH than the corresponding peeled carrots (Table 4, Fig.…”
Section: Spatial Distribution Of Polyacetylenes In Carrotssupporting
confidence: 83%
See 2 more Smart Citations
“…www.jss-journal.com centration levels of polyacetylenes found in the present study were within the levels previously reported in peeled carrots [13,34]. The carrot peel contained over a ten-fold higher concentration of FaDOH than the corresponding peeled carrots (Table 4, Fig.…”
Section: Spatial Distribution Of Polyacetylenes In Carrotssupporting
confidence: 83%
“…By detecting the compounds at 205 nm, the UV sensitivity is improved approximately ten times and consequently the detection and quantification limits of the polyacetylenes. This is especially important as the concentration in carrots can be relatively low i. e. less than 5 mg/kg FW [13,14,34]. However, many other compounds also absorb UV light at 205 nm and this is particularly the case in carrot root extracts.…”
Section: Chromatographymentioning
confidence: 96%
See 1 more Smart Citation
“…The total amount of polyacetylenes was highest in Line 2 (9.11 mg/100 g FW) and lowest in Nairobi (5.54 mg/100 g FW). The concentration levels of polyacetylenes were within the levels previously reported in peeled carrots (Lund & Bruemmer, 1991;Hansen et al, 2003;Czepa & Hofmann, 2004;Kidmose et al, 2004;. Many factors may have a significant impact on the polyacetylene content in carrots e.g.…”
Section: Polyacetylenesmentioning
confidence: 65%
“…Moreover, abiotic factors, such as mechanical stress, is reported to increase the amounts of the key bitter tastants, members of the C17-polycetylenes, present in native carrots (Daucus carota L.) to efficiently high concentrations, causing a bitter off-flavor is perceived, occurring especially often during the production process for infant diet carrot products [79,80,[91][92][93][94][95][96][97][98]. In addition, a decrease in flavor quality accompanied by an increase in bitter taste has also been reported in raw hazelnuts (Corylus avellana L.) upon biotic stress challenges, such as upon infection by bugs, belonging to the hemipteran family, like Gonocerus acuteangulatus and Coreus marginatus [99].…”
Section: Sensomics -A Phenotyping Tool To Characterize Crops Flavor Imentioning
confidence: 99%